The Effectiveness the Power of Two in Speaking Skill in Describing Pictures at the Second Years of Madrasah Nurul As’adiyah Callaccu Sengkang. - As'ad, Muhammad (Prosiding University Research Colloquium, 2019)
Background: This research was about the effectiveness the power of two in describing pictures in speaking skill at the second years of Madrasah Nurul As’adiyah Callaccu Sengkang. The study tried to answer the problem: “what was effective is the power of two in describing pictures in enhancing student’s speaking skill?” Purpose: The objectives of the research were to find out the effectiveness the power of two in describing pictures in enhancing students’ speaking skill. Method: This research used pre experimental method. The population of this research was the second years students of Madrasah Nurul As’adiyah Callaccu Sengakang Kabupaten Wajo in academic years 2013/2014. The total number of the population was 70 students. The sample of the research was selected by using purposive sampling technique. The total numbers of sample were 30 students. The instrument of this research was speaking test including pre-test and post-test. After several meetings, this research found out that the used of the power of two in describing pictures was effective to enhance the students’ speaking skill. Result: The result of this research was the mean score obtained by the students through the pre-test was 40,18 and post-test was 55,18. The t-test value was higher than t-table (7,31> 2.045). It means that there was a significant difference between the result of the students’ pre-test and post-test. Therefore, hypothesis H0 was rejected and H1 was accepted. It could be said that using the power of two in describing pictures is effective to enhance the students’ speaking skill at Madrasah Nurul As’adiyah Callaccu Sengkang. Based on the data above, the researcher concluded that the power of two in describing picture was effective to enhance the students’ speaking skill. Therefore, the researcher suggests to English teacher to use the power of two in describing picture as media in teaching speaking skill.